PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN PROBLEM BASED LEARNING UNTUK MENGURANGI KECEMASAN MATEMATIKA DAN MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MTs - Setiani, Ana (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2016)
The   aims   of   this   research   are focused  to  examine  the  effect  of  learning model      was      estimated      to      decrease mathematics    anxiety    and    to    increase student's    mathematical    problem    solving ability.  The  instrument  that  used  for  this research were ability test of problem solving in math and mathematics quosionaire with likert  scale.  The  data  analysis  used  mixed method embedded konkruen method. Based on  data  analysis  concluded  (1)  the  result show the increasing student's mathematical problem  solving  ability  by  problem  based learning  model  better  than  by  expository teaching; (2) increasing quality of studen'ts mathematical   problem   solving   ability   by problem   based   learning   better   than   by expository      teaching.      (3)      significant differences between mathematics anxiety and the accomplisment of student's matematical problem  solving  ability  by  problem  based learning  and  by  expository  teaching  (4) significant  differences  between  decreasing mathematics   anxiety   and   increasing   of student's    mathematical    problem    solving ability  by  problem  based  learning  and  by expository   teaching.    and    (5)   there   is significan relationship between mathematics anxiety and the accomplishment of student's mathematical problem solving ability.